Comparative evaluation of the masking ability of lithium disilicate ceramic with different core thickness on the shade match of indirect restorations over metallic substrate: An In vitro study - Priyadarshini Thilagar; Jayakrishnakumar Sampathkumar; Chitra Shankar Krishnan; Hariharan Ramakrishnan; Hariharan Ramasubramanian; N S Azhagarasan (Wolters Kluwer Medknow Publications, 2019)
Purpose: The purpose of this in vitro study was to comparatively evaluate the masking ability of lithium disilicate ceramic with different core thickness on the shade match of indirect restorations over metallic substrate. Materials and Methods: A total of 30 heat pressed lithium disilicate ceramic discs of low translucency were fabricated with diameter 10mm and thickness of 1 mm, 1.3 mm and 1.6mm with each thickness consisting of 10 samples to be used in the study. Thirty Ni-Cr metal discs of diameter 10mm were used to simulate metallic substrates .The colour difference of the lithium disilicate ceramic disc before and after cementation were measured using CIE LAB system. Results: The mean colour difference (ΔE) of Group I,Group II, Group III before cementation with the Ni-Cr metal discs was 17.32,13.01 and 11.73 respectively. The mean colour difference (ΔE) of Group I,Group II, Group III after cementation with the Ni-Cr metal discs was 16.32,12.10, 11.05 respectively. Conclusion: The mean colour difference of the three groups were found to be more than the clinically acceptable perceptibility threshold (ΔE < 3.3) indicative of reduced masking ability of all the three groups of ceramic discs over metallic substrate used in this study.